Nietzsche and modern German thought - Ansell-Pearson, Keith, 1960- (Routledge, 2002)
Nietzsche is no longer a marginal figure in the study of philosophy. This collection of specially commissioned essays reflects the emergence of a serious interest amongst philosophers, sociologists and political theorists. By considering Nietzsche's ideas in the context of the modern philosophical tradition from which it emerged, his importance in contemporary thought is refined and reaffirmed. Modern German thought begins with Kant and has rarely escaped his influence. It is with respect to this Kantian heritage that this volume examines Nietzsche. These essays critically consider Nietzsc.